Optimal Employee Productivity: Understanding the Influence of Competence, Wages, and Communication - Ummul Maulidah; Vera Firdaus; Dewi Andriani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the relationship and influence of competence, wages, and communication on employee productivity at PT. Karya Alfa Omega. The type of research conducted by the author is quantitative descriptive research. In this quantitative descriptive research, purposive sampling was used as the data collection method involving 100 respondents. The data were analyzed using SmartPLS 5.0 software, including Outer Model Test Analysis, Validity Test, Reliability Test, Average Variance Extracted (AVE) Test, R-square Test, and Hypothesis Test. The results show that competence positively affects employee productivity (T=2.007, p=0.045), wages positively affect employee productivity (T=2.042, p=0.041), and communication also positively affects employee productivity (T=2.053, p=0.040). This study provides new empirical insights into the interaction between competence, wages, and communication, emphasizing their impact on employee productivity. The results show that employee productivity at PT. Karya Alfa Omega needs to be improved through skills training, facility improvements, and fulfillment of employee rights. Competence, wages, and communication are also influential factors.